R&D importance in improving automobile trading market - Mickonytė, Aurelija; Melnikas, Borisas (Business, Management and Economics Engineering, 2010)
Production and sales of automobiles are significant parts of the 21st century economy. The aim of this study is to reveal the latest and most perspective scientific research directions in improving international automobile trading business by using scientific sources and official statistics. Scientific researchers are focused on strategic means that have to be taken in order to recover the market share and past sales volumes.This study reveals that even though sales volumes of automobiles in general are decreasing rapidly, sales of compact class automobiles are improving. Three main reasons for this fact are stated. First is price, second is the model of automobile and its technical characteristics, third reason is growing environmentalism. Regarding the mentioned reasons for automobile market over grouping by segments, three main scientific research directions are discussed: those that are due to price reduction, technical appearance focused and environment focused scientific researches.Article in Lithuanian.Perspektyvūs moksliniai tyrimai, skirti tarptautiniam prekybos automobiliais verslui plėtoti